FENOMENA JASA TITIP BELI (JASTIP) SEBAGAI BENTUK BUDAYA KONSUMTIF MASYARAKAT PADA MASA PANDEMI COVID-19 - Fitrianatsany Fitrianatsany (Universitas Wijaya Kusuma Surabaya, 2022)
The buying and selling service (Jastip) is a new symptom of Indonesian society. Jastip is a bridge for online shoppers who want to shop, from teenagers, and new rich people to socialite mothers. Especially during the Covid-19 pandemic, jastip has actually become a new style for consumers to shop without the need to leave the house, in addition to not being tired, to minimize the spread of Covid-19. This article will explore these symptoms as part of the consumptive culture of society, especially during the Covid-19 pandemic. The results of this study indicate that the culture of shopping through courier services cannot be separated from what Jean Baudrillard calls a mode of consumption. As for the meaning, this phenomenon is also interpreted as a way to raise one's social status. By using certain products or brands, they feel that others will respect them. Keywords: Jastip, Behavior, Consumptive Culture, Society.